2014
DOI: 10.1177/1756285614528064
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran etexilate for secondary stroke prevention: the first year experience from a multicenter short-term registry

Abstract: Background: There are growing concerns for the side effects of dabigatran etexilate (dabigatran), including higher incidence of dyspepsia and gastrointestinal bleeding. We conducted a multicenter early implementation study to prospectively evaluate the safety, efficacy and adherence to dabigatran for secondary stroke prevention. Methods: Consecutive atrial fibrillation (AF) patients with ischemic stroke (IS) or transient ischemic attack (TIA) received dabigatran for secondary stroke prevention during their hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
4
1
1
Order By: Relevance
“…Even more alarmingly, the rate of major gastrointestinal bleeding was 4.11%/year in our cohort, substantially higher than that of both the Asian (0.96%/year to 1.15%/year) and non-Asian population (1.14%/year to 1.69%/year) in the RE-LY study [21]. While some studies in the real world setting documented very few bleeding events, ranging from 3.3% to 5.2%,[16], [18], [22] Michel and colleagues revealed that 29% of patients receiving dabigatran had experienced bleeding events, predominantly minor ones [23]. In particular, Ho and colleagues reported the total bleeding and intracranial hemorrhagic risks of 22.95% and 1.64%, respectively, which were even higher than that in our cohort [17].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Even more alarmingly, the rate of major gastrointestinal bleeding was 4.11%/year in our cohort, substantially higher than that of both the Asian (0.96%/year to 1.15%/year) and non-Asian population (1.14%/year to 1.69%/year) in the RE-LY study [21]. While some studies in the real world setting documented very few bleeding events, ranging from 3.3% to 5.2%,[16], [18], [22] Michel and colleagues revealed that 29% of patients receiving dabigatran had experienced bleeding events, predominantly minor ones [23]. In particular, Ho and colleagues reported the total bleeding and intracranial hemorrhagic risks of 22.95% and 1.64%, respectively, which were even higher than that in our cohort [17].…”
Section: Discussioncontrasting
confidence: 57%
“…Similarly, Miyamoto and colleagues observed that discontinuation of dabigatran was mainly due to dyspepsia, followed by deteriorating renal function, then minor bleeding [16]. On the other hand, a multi-center study reported that high cost accounted for half of the discontinuation whereas gastrointestinal side effects such as dyspepsia and flatulence came next [18]. Of note, dabigatran-induced dyspepsia was much more common in the present cohort than in the RE-LY study (16.5% vs. 11.8% in patients prescribed dabigatran 110 mg two times daily, and 11.3% in those prescribed 150 mg two times daily) [11].…”
Section: Discussionmentioning
confidence: 95%
“…Our previous short-term experience with the use of DE for secondary stroke prevention in NVAF patients has been recently reported [10]. All haemostatic parameters were analyzed before and after treatment with DE.…”
Section: Study Populationmentioning
confidence: 99%
“…Various studies have shown different results for the correlation between the costs of dabigatran and long-term persistence. 35,36 To some extent, health insurance played an important part in averting economic hardship and improving medication adherence. 13,37 In China, the high cost of dabigatran, coupled with a lack of medical insurance coverage added to the economic burden, which was a very important factor for dabigatran discontinuation.…”
Section: Predictors Of Dabigatran and Warfarin Discontinuationmentioning
confidence: 99%